'History in conflict: Israeli–Palestinian speeches at the United Nations, 1998–2016'. Issue 4 (7th August 2020) - Pressman, Jeremy
ABSTRACT: A close textual study of Israeli and Palestinian speeches at the annual UN General Debate from 1998 to 2016 demonstrates how conflict is embedded in historical presentations. At the same time, the exclusionary, zero-sum history in these UN speeches becomes one of several obstacles for moving from conflict to conflict resolution. Conflict and history's public manifestations are mutually reinforcing. From a thematic perspective, Israeli leaders talk about victimization, existential insecurity, and ancient Jewish roots. Palestinian leaders covered a similar range: the Nakba (catastrophe) of 1948, existential insecurity, and right and justice. While neither party directly delegitimizes the other's nationalism at the United Nations, both sides trumpet their own commitment to peace and the other's peace failings. From a symbolic perspective, the article addresses the numerical base of Palestinian speeches, UN Resolutions 181 and 194, and Arab–Israeli Wars in 1948 and 1967, and how they relate to land and demographic disputes. In conclusion, the article suggests how a conciliatory history that opens the door to conflict resolution, or itself is a sign that the door has been opened, might read.